Functional outcomes and quality of life following tumour-related hemipelvectomy - a decade of HUSM experience - Sharifudin, Mohd Ariff; Wan, Zulmi; Wan Ismail, Wan Faisham Numan; Mat Zin, Nor Azman; Mohamed Amir, Nawaz Hussain (2012)
Introduction: Although great advancements in survival over the last half century have been made with adjuvant therapies and current surgical techniques, pelvic resections as the surgical treatment for pelvic tumours continue to have significant associations with morbidity and complications. We evaluated patients underwent tumour-related hemipelvectomy in our institution between year 2001-2010. Patients and Methods: Functional outcomes were evaluated using the Enneking’s criteria as adopted by the Musculoskeletal Tumor Society (MSTS). Patients who had surgery at any point in their clinical course were included in this study. Patients with follow up period of less than six months were not included. MSTS scores were obtained on the most recent follow-up after the surgery. Survivors were evaluated using the European Organization for Research and Treatment of Cancer Core Quality-of-Life Questionnaire (EORTC QLQ-C30) for quality-of-life measurement. Results: A total of 40 patients following internal or external hemipelvectomy were included in this study. The mean age is 38.3 years (range 13 to 79). Both genders were equal in number. Mean duration of follow-up was 33.7 months (range 6 to 110 months). The mean MSTS percentage score was 54.67% (range 10.00% to 100.00%). The best functional results were seen after pelvic resection with preservation of hip joint. All external hemipelvectomy patients had poor functional outcome. Longer duration of follow-ups, good pre-operative performance status and early ambulation after surgery were associated with higher functional score. Good functional outcomes in limb-salvage surgery ensured the ability of patients to return to previous job. Quality of life of survivors was comparable with the general population, except for role functional scale. Conclusion: Functional outcomes were significantly affected by the surgery. However, major tumour-related hemipelvectomy is justified with proper indication and selection of patients. This study is an effort to obtain a proper reference for preoperative discussion with patient and relatives regarding expected outcomes following such a procedure.